2022
DOI: 10.3390/ijms232112922
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheet-Facilitated Spray Delivery of dsRNAs Represents a Potential Tool to Control Rhizoctonia solani Infection

Abstract: Rhizoctonia solani is one of the important pathogenic fungi causing several serious crop diseases, such as maize and rice sheath blight. Current methods used to control the disease mainly depend on spraying fungicides because there is no immunity or high resistance available in crops. Spraying double-strand RNA (dsRNA) for induced-gene silencing (SIGS) is a new potentially sustainable and environmentally friendly tool to control plant diseases. Here, we found that fluorescein-labelled EGFP-dsRNA could be absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…According to Mitter et al (Mitter et al, 2017), spray-delivered CMV2b-dsRNA-Cy3 was washed off by irrigation and sudden rain, but CMV2b-dsRNA-Cys3-LDH with NPs was still adhered to the leaves and offered better crop protection against the pathogen. Similar observation were reported where the dsRNA-LDH complex showed stronger and more lasting effects in controlling Rhizoctonia solani infection by targeting pathogenicity-related genes by SIGS than using dsRNA alone (Chen et al, 2022). Overall, the NPs loaded dsRNA have been found effective against numerous phytopathogenic fungi e.g., Rhizoctonia solani, Fusarium oxysporum, Sclerotinia sclerotiorum, Sclerotium rolfsii, Colletotrichum spp., etc.…”
Section: Introductionsupporting
confidence: 82%
“…According to Mitter et al (Mitter et al, 2017), spray-delivered CMV2b-dsRNA-Cy3 was washed off by irrigation and sudden rain, but CMV2b-dsRNA-Cys3-LDH with NPs was still adhered to the leaves and offered better crop protection against the pathogen. Similar observation were reported where the dsRNA-LDH complex showed stronger and more lasting effects in controlling Rhizoctonia solani infection by targeting pathogenicity-related genes by SIGS than using dsRNA alone (Chen et al, 2022). Overall, the NPs loaded dsRNA have been found effective against numerous phytopathogenic fungi e.g., Rhizoctonia solani, Fusarium oxysporum, Sclerotinia sclerotiorum, Sclerotium rolfsii, Colletotrichum spp., etc.…”
Section: Introductionsupporting
confidence: 82%
“…These fungi cause a fusarium crown and root rot disease in tomatoes. Researchers from China found that RsCRZ1-dsRNA-LDH induced stronger RNAi than RsCRZ1-dsRNA to control the growth of Rhizoctonia solani (Chen et al, 2022).…”
Section: Potential Of Bioclay™ As a Plant Protectant Against Fungal I...mentioning
confidence: 99%
“…Talking about nanomaterial-based delivery of dsRNA, the LDH nanosheet is one of the most powerful and efficient processes to spray RNAi on A. thaliana leaves. CMV2b-dsRNA-Cy3 got erased by sudden rain and irrigation, whereas CMV2b-dsRNA-Cys3-LDH was still attached to its leaves, providing better crop protection against the pathogens …”
Section: Spray Induced Gene Silencingmentioning
confidence: 99%
“…CMV2b-dsRNA-Cy3 got erased by sudden rain and irrigation, whereas CMV2b-dsRNA-Cys3-LDH was still attached to its leaves, providing better crop protection against the pathogens. 62 Sclerotinia sclerotiorum is another pathogen that can be reduced by SIGS application infecting thale cress and oil rape seed plants.…”
Section: Spray Induced Gene Silencingmentioning
confidence: 99%